Revenue Generation: Itas Impact on Government Developmental Effort (A Study Of Selected Local Council In KOGI East Senatorial District) (Global Journal of Management and Business Research, 2013)
Local government is faced with varieties of difficulties to source adequate revenue from federal government, state government and internally generated revenue; such problems are cogwheel to the smooth running of local government administration. Thus, the objective of the research was to analyze the extent to which revenue generation had affected the development of the selected local Governments. The researcher used both primary and secondary methods of data collection to generate the needed data. The data obtained through secondary data were analyzed using simple least square regression method (spss version17). The following were some of the findings which included the following; there is a significant relationship between revenue generated and developmental effort of government, poor development of the areas, lack of basic social amenities to the rural people and lack of revenue to maintain the existing infrastructures. The researcher therefore recommended that the local government should provide basic amenities of high quality. By doing so, the people's interest would be geared towards giving their maximum support to the local government which would lead to the development of the rural area?
Keywords: development; projects; revenue; generation; government